2019
DOI: 10.1111/1742-6723.13248
|View full text |Cite
|
Sign up to set email alerts
|

Effective triage in the Pacific region: The development and implementation of the Solomon Islands Triage Scale

Abstract: Objective The ED at the National Referral Hospital in Honiara, Solomon Islands, receives approximately 50 000 patients per year. A 2014 review of ED functioning identified deficiencies in triage processes. Placement of Australian volunteer advisors provided an opportunity to develop and implement a purpose‐designed triage system. Methods Action research methodology and the ‘plan, act, observe, reflect’ cycle was employed, leading to the development of a three‐tier triage system based on the South African Triag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…Publications from the region provide insights into EC needs and demonstrate how effective interventions can be developed and implemented at low cost. In Fiji, trauma management has been improved through enhanced surveillance and team‐based care; in Papua New Guinea, action research has helped optimise asthma treatment; and in the Solomon Islands, inconsistent triage (a challenge in many Pacific Island countries) has been addressed by a simple, locally developed triage system . Despite experiencing significant disasters, Indonesia and Myanmar have only recently developed specialty training in emergency medicine (EM) and have identified that the crucial pre‐hospital EC needs can be assisted by simple rural systems and basic protocols …”
Section: Ec and The Indo‐pacificmentioning
confidence: 99%
“…Publications from the region provide insights into EC needs and demonstrate how effective interventions can be developed and implemented at low cost. In Fiji, trauma management has been improved through enhanced surveillance and team‐based care; in Papua New Guinea, action research has helped optimise asthma treatment; and in the Solomon Islands, inconsistent triage (a challenge in many Pacific Island countries) has been addressed by a simple, locally developed triage system . Despite experiencing significant disasters, Indonesia and Myanmar have only recently developed specialty training in emergency medicine (EM) and have identified that the crucial pre‐hospital EC needs can be assisted by simple rural systems and basic protocols …”
Section: Ec and The Indo‐pacificmentioning
confidence: 99%
“…• Key national hospital, Ministry of Health and Australian Government Aid stakeholders all accepted the core findings of the 2014 Needs Assessment and concurred with the recommendations that prioritised leadership, staff improvements, triage, paediatric care and attention to overcrowding and patient flow • Components from the 2014 Needs Analysis that have been considered and acted upon since delivery to the stakeholders: (Table 3) o development and implementation of a new triage scale [33] o creation of a paediatric EC area within the ED o new protocols for managing ED overcrowding and patient flow o sustained support for local leadership and staff education.…”
Section: Construct Validitymentioning
confidence: 77%
“…Therefore, although emphasis for action differed in each site, it is likely that even small improvements in a single domain positively influenced overall EC delivery at each facility. Highlights of subsequent outcomes catalysed by the Needs Assessment process include the development and implementation of the Solomon Islands Triage Scale [33], multidisciplinary EC improvement activities in Kiribati [34] and ongoing program support in Timor-Leste [35].…”
Section: Discussionmentioning
confidence: 99%
“…Across Pacific emergency care settings, the capacity of systems and processes to effectively manage patient presentations and flow is varied [ 10 ]. Nursing staff are often omitted from health system planning and development in disaster situations [ 12 ], but recent reforms have facilitated greater nursing involvement in COVID-19 response [ 13 ].…”
Section: Systemsmentioning
confidence: 99%
“…The new process has improved communication between pre-hospital staff and emergency nurses and refined the movement of patients from ambulance arrival through to emergency via triage. Having an existing functional triage system, the Solomon Islands Triage Scale [ 13 ], meant that ED nursing staff were already familiar with triage systems and have been able to easily adapt to working in the COVID-19 triage centre.…”
Section: Systemsmentioning
confidence: 99%